Membrane lipid sensitivity to ocean warming and acidification poses a severe threat to Arctic pteropods - Lischka, Silke; Greenacre, Michael J.; Riebesell, Ulf; Graeve, Martin (Frontiers in Marine Science, 2022)
Ocean warming and acidification will be most pronounced in the Arctic. Both phenomena severely threat thecosome pteropods (holoplanktonic marine gastropods) by reducing their survival (warming) and causing dissolution of their aragonitic shell (acidification). Lipids, particularly phospholipids, play a major role in veligers and juveniles of the polar thecosome pteropod Limacina helicina (Phipps 1774) comprising over two thirds of their total lipids. Membrane lipids (phospholipids) are important in temperature acclimation of ectotherms. Hence, we experimentally investigated ocean warming and acidification effects on total lipids, lipid classes and fatty acids of Arctic early-stage L. helicina. Temperature and pCO2 treatments chosen resembled Representative Concentration Pathway model scenarios for this century. We found a massive decrease of total lipids at elevated temperature and at the highest CO2 concentration (1100 $μ$atm) of the in situ temperature. Clearly, temperature was the overriding factor. Total lipids were reduced by 47--70%, mainly caused by a reduction of phospholipids by up to 60%. Further, based on pHT development in the incubation water of pteropods during the experiment, some evidence exists for metabolic downregulation (shutdown?) in pteropods at high factor levels of temperature and pCO2. Consequently, cell differentiation and energy balance of early-stage larvae was probably severely compromised. Comparison of our experimental with 'wild' organisms suggests phospholipid reduction to values clearly outside natural variability. Based on the well-known significance of phospholipids for membranogenesis, early development, and reproduction, negative warming effects on such a basal metabolic function may be a much more immediate threat for pteropods than so far anticipated shell dissolution effects due to acidification.